The Effect of Organizational Culture, Work Stress, and Organizational Commitment on Organizational Citizenship Behavior Mediated by Job Satisfaction - Hery Winoto Tj; Melitina Tecoalu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Employee initiative is an important thing that every company or organization in all business industries wants to have. Initiatives play an essential role in improving company performance, which will add value to the company in the long run. The more employees in a company who have a high level of initiative towards their work, the better company performance will be. The goals of this research is to analyze the impact of organizational culture, works stress, organizational commitment mediated by job satisfaction on orga nizational citizenship behavior at PT GCM. We used non-probability sampling technique and SmartPLS tools to analyzing the data. Using the purposive sampling technique, we obtained 60 respondent data. Our results show that organizational culture, work stress, and organizational commitment directly influence organizational citizenship behavior, and job satisfaction also has a mediating role in the relationship between organizational culture, work stress, organizational commitment, and organizational citizenship behavior.